Evaluasi Keterlaksanaan Sistem Inventori Sayuran Perishable di Restoran Pavilion JW Marriott Surabaya - Felando, Marvinius; Purwidiani, Niken; Romadhoni, Ita Fatkhur; Restami, Mafisa (Indo-MathEdu Intellectuals Journal, 2026)
This study aims to evaluate the implementation of the perishable vegetable inventory system at Pavilion Restaurant, JW Marriott Surabaya. The research employed a qualitative descriptive approach using observation and interviews involving three groups of research subjects, namely receiving staff, the Chef In Charge, and kitchen staff directly involved in vegetable inventory management. The collected data were analyzed using qualitative descriptive analysis techniques, which included data reduction, data presentation, and conclusion drawing. The results indicate that the inventory system has generally been implemented in accordance with standard operating procedures, particularly in the stages of receiving and storage, as reflected in quality inspection practices, chiller temperature control, the application of first in first out (FIFO) or first expired first out (FEFO), and the use of appropriate packaging. However, several challenges were identified, including inconsistent temperature recording, the absence of a documented issuing system, and the implementation of the min–max and reorder system that has not yet been fully based on actual usage data. In addition, human resource factors were found to influence the consistency of procedure implementation. Therefore, strengthening record-keeping practices, data-based inventory control, and the role of human resources is necessary to improve the efficiency and sustainability of inventory management.